2017
DOI: 10.1038/onc.2017.42
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp63α promotes adhesion of metastatic prostate cancer cells to the bone through regulation of CD82

Abstract: ΔNp63α is a critical mediator of epithelial development and stem cell function in a variety of tissues including the skin and breast, while overexpression of ΔNp63α acts as an oncogene to drive tumor formation and cancer stem cell properties in squamous cell carcinoma. However, with regards to the prostate, while ΔNp63α is expressed in the basal stem cells of the mature gland, during adenocarcinoma development, its expression is lost and its absence is used to clinically diagnose the malignant state. Surprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“… 23 , 24 PC3 is a bone metastatic PCa cell line, which promotes high osteolytic lesions with minimal or no osteoblastic function. 25 , 26 Osteoclast precursors were isolated from the bone marrow of C57BL6 mice (forelimbs and hind limbs) and were differentiated using RANKL and M-CSF (control condition) and conditioned medium (CM) from PC3 and LNCaP C4-2B cells separately. M-CSF and RANKL signaling is central to osteoclast differentiation under physiological condition.…”
Section: Resultsmentioning
confidence: 99%
“… 23 , 24 PC3 is a bone metastatic PCa cell line, which promotes high osteolytic lesions with minimal or no osteoblastic function. 25 , 26 Osteoclast precursors were isolated from the bone marrow of C57BL6 mice (forelimbs and hind limbs) and were differentiated using RANKL and M-CSF (control condition) and conditioned medium (CM) from PC3 and LNCaP C4-2B cells separately. M-CSF and RANKL signaling is central to osteoclast differentiation under physiological condition.…”
Section: Resultsmentioning
confidence: 99%
“…The other isoform is the ΔN isoform, which is predominantly expressed in the basal epithelial layer of mammary glands, skin, esophagus, and prostate [4][5][6][7][8], and plays key roles in tissue homeostasis. Additionally, ΔNp63 can have oncogenic functions in a number of cancers including breast, prostate, and head squamous cell carcinoma [4,[9][10][11]. In our earlier study, we found that ΔNp63 is critically involved in maintaining the stem-like/basal state of the mammary epithelium in normal development and basal breast cancer via activation of Wnt signaling [4].…”
Section: Abstract: δNp63; Mammary Gland; Oxphos; Polarity; Stem Cellsmentioning
confidence: 94%
“…Sustained expression of ∆Np63α tends to promote the well-differentiated SCC phenotype and restricts epithelial–mesenchymal transition induced by TGF-β [ 42 ]. However, both suppressive [ 43 45 ] and promotive roles [ 46 ] of ∆Np63α in cell invasion and metastasis have been demonstrated in various cell contexts, suggesting a cell context-specific role in cancer metastasis. Growing evidence demonstrates that ΔNp63 exerts both a suppressive and promotive role on target genes expression [ 47 49 ].…”
Section: Introductionmentioning
confidence: 99%